2021
DOI: 10.1016/j.omto.2021.09.005
|View full text |Cite
|
Sign up to set email alerts
|

CD47-targeted cancer immunogene therapy: Secreted SIRPα-Fc fusion protein eradicates tumors by macrophage and NK cell activation

Abstract: CD47 protects healthy cells from macrophage attack by binding to signal regulatory protein α (SIRPα), while its upregulation in cancer prevents immune clearance. Systemic treatment with CD47 antibodies requires a weakened Fc-mediated effector function or lower CD47-binding affinity to prevent side effects. Our approach combines “the best of both worlds,” i.e., maximized CD47 binding and full Fc-mediated immune activity, by exploiting gene therapy for paracrine release. We developed a plasmid vector encoding fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…4 ): (1) Using the strategy of CD47 antagonist prime and maintenance dosing ( e.g ., 5F9 and IBI-188); (2) Modifying the drug structure of CD47 monoclonal antibody (e.g ., AO-176, TJ011133, SRF231, and AK117); (3) Fusion protein of CD47/SIRPa combining with different antibodies, such as CD20, CD19, could be of a promising strategy in the immunotherapy targeting CD47/SIRPa axis ( e.g. , IMM0306, NI-1701) [ 17 , 74 ]; (4) Development of SIRPα/Fc fusion protein antibodies; (5) Development of small-molecule inhibitors ( e.g ., RRX-001, QPCTL antibodies); (6) Introduction of new drug delivery methods ( e.g ., CD47 nanobody [ 55 ], plasmid vector [ 75 ], and CD47/SIRPα blocking peptide [ 76 ]); (7) Since binding of CD47 to SIRPγ enables T cell activation and proliferation [ 5 ], blockade of SIRPα-CD47 interaction while preserving SIRPγ binding to CD47 may be a strategy for cancer immunotherapy ( e.g. , SIRP-1 and SIRP-2) [ 77 ]; (8) SIRPα engages with CD47 in either cis or trans behavior in different scenarios.…”
Section: Challenges and Future Perspectives Of Cd47/sirpα Immune Chec...mentioning
confidence: 99%
See 1 more Smart Citation
“…4 ): (1) Using the strategy of CD47 antagonist prime and maintenance dosing ( e.g ., 5F9 and IBI-188); (2) Modifying the drug structure of CD47 monoclonal antibody (e.g ., AO-176, TJ011133, SRF231, and AK117); (3) Fusion protein of CD47/SIRPa combining with different antibodies, such as CD20, CD19, could be of a promising strategy in the immunotherapy targeting CD47/SIRPa axis ( e.g. , IMM0306, NI-1701) [ 17 , 74 ]; (4) Development of SIRPα/Fc fusion protein antibodies; (5) Development of small-molecule inhibitors ( e.g ., RRX-001, QPCTL antibodies); (6) Introduction of new drug delivery methods ( e.g ., CD47 nanobody [ 55 ], plasmid vector [ 75 ], and CD47/SIRPα blocking peptide [ 76 ]); (7) Since binding of CD47 to SIRPγ enables T cell activation and proliferation [ 5 ], blockade of SIRPα-CD47 interaction while preserving SIRPγ binding to CD47 may be a strategy for cancer immunotherapy ( e.g. , SIRP-1 and SIRP-2) [ 77 ]; (8) SIRPα engages with CD47 in either cis or trans behavior in different scenarios.…”
Section: Challenges and Future Perspectives Of Cd47/sirpα Immune Chec...mentioning
confidence: 99%
“…(5) Development of small-molecule inhibitors (e.g., RRX-001, QPCTL antibodies); (6) Introduction of new drug delivery methods (e.g., CD47 nanobody [55], plasmid vector [75], and CD47/SIRPα blocking peptide [76]); (7) Since binding of CD47 to SIRPγ enables T cell activation and proliferation [5], blockade of SIRPα-CD47 interaction while preserving SIRPγ binding to CD47 may be a strategy for cancer immunotherapy (e.g., SIRP-1 and SIRP-2) [77]; (8) SIRPα engages with CD47 in either cis or trans behavior in different scenarios. SIRPα expressed in macrophages exhibits trans binding to CD47 that are expressed in other types of 'self ' cells, leading to local SIRPα accumulation and inhibition of 'self 'cell engulfment including the tumor cells [35,78].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…CD47 is overexpressed on BC cells, which inhibits macrophage phagocytosis through binding itself to its receptor, SIRPα 135 . Targeting the CD47 / SIRPα axis not only blocks innate immune but also causes T‐cell activation 136,137 . Monotherapy by CD47 blockade leads to a reduction in tumor growth and an increase in OS 138 .…”
Section: Therapeutic Strategies Targeting Tams For Bcmentioning
confidence: 99%
“…(3) NK cells mediate the ADCC effect: although NK cells express less SIRPα, tumor cells can still inhibit the function of NK cells through the CD47-SIRPα interaction, and the disruption of the CD47-SIRPα axis restores NK cell function . Several studies have shown that aCD47 and SIRPα fusion protein can activate NK cell FcγR to exert the ADCC effect. (4) aCD47 can directly induce tumor cell apoptosis in a caspase-independent manner …”
Section: Therapy Strategies Targeted On the Cd47-sirpα Axismentioning
confidence: 99%